Virtual environments in teaching training as a teaching mediation of the I.E. of fourth grade of primary of the North Ugel - Silvia Dolores Quispe Flores (2019)
This research was analyzed, the results of the years 2007 - 2014 implemented by the Regional System of Evaluation of Learning (RSV), the results showed the gap of children not reached a satisfactory level in reading comprehension and mathematics, the regional scope database corresponding to the North UGEL was used to carry out the data, from this information obtained, bibliographic material on virtual environments that support the improvement of the teaching- learning process in teachers was analyzed, We came to show the positive effects of the use of digital tools in the application of the program. In the last five years a set of strategies has been working to improve the levels of reading and math comprehension in the students of second and fourth grade of primary school in the educational institutions of the northern Arequipa, however they are still in a 40% in the process level, not achieving the minimum capacitiesand performances towards the achievement of the competences of the area of mathematics and communication, being the problem the use of teaching and learning strategies pertinent to achieve the competences at a satisfactory level, it is thus One of the means to achieve the effectiveness of the strategy is the use of virtual environments. general objective to strengthen the teaching training of the mediation of education with the use of virtual environments through theimplementation of the project “Improving the quality of the educational service to increase the achievement of learning in communication and mathematics in students of Public Educational Institutions of the primary level, corresponding to the scope of intervention of the UGEL North ”and has as specific objectives: a) Analyze the management of virtual environments as teaching measurement tools, b) Analyze the factors that influence the improvement of theirprofessional training with the use of virtual environments. Selection of the teaching participants who participated in the following stages of the project “Improving the quality of the educational service to increase the achievement of learning in communication and mathematics in students of Public Educational Institutions of the primary level, corresponding to the scope of intervention of the North UGEL. The following interventions are performed: 1 Platform use, 2 Use of educational software, 3 Use of videos in teacher internships, 4 Training in curriculum planning and virtual environment management, 5 Monitoring and Accompaniment, Sample: A random sample of all the EIs of the northern primary education gel was selected, with a sample of 84 EI corresponding to 84 teachers and 10 directors As for the results In the answers of the 82 teachers and principals surveyed, 34% (28 of the 82 evaluated) said that the pedagogical strategies have improved the learning of their students.